2019
DOI: 10.1002/jcb.28463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell source and osteoblast differentiation on gene expression profiles of mesenchymal stem cells derived from bone marrow or adipose tissue

Abstract: Mesenchymal stem cells (MSCs) have been used in therapies for bone tissue healing. The aim of this study was to investigate the effect of cell source and osteoblast differentiation on gene expression profiles of MSCs from bone marrow (BM-MSCs) or adipose tissue (AT-MSCs) to contribute for selecting a suitable cell population to be used in cell-based strategies for bone regeneration. BM-MSCs and AT-MSCs were cultured in growth medium to keep MSCs characteristics or in osteogenic medium to induce osteoblast diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
(129 reference statements)
0
12
1
3
Order By: Relevance
“…For example, canine ADMSCs have higher differentiation potential than MSCs from bone marrow, umbilical cord, amniotic membrane, or placenta ( 21 ). In contrast, in horses, chondrogenic ( 69 ) and osteogenic potentials ( 70 ) seem higher in bone marrow MSCs than in ADMSCs. These results indicate the possibility that MSCs from different animals have different properties indeed.…”
Section: Discussionmentioning
confidence: 83%
“…For example, canine ADMSCs have higher differentiation potential than MSCs from bone marrow, umbilical cord, amniotic membrane, or placenta ( 21 ). In contrast, in horses, chondrogenic ( 69 ) and osteogenic potentials ( 70 ) seem higher in bone marrow MSCs than in ADMSCs. These results indicate the possibility that MSCs from different animals have different properties indeed.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, it has been found to play a role in the regulation of stem cell density and neural differentiation during adult neurogenesis [35]. The next gene, IGSF10, has been previously detected to be upregulated during osteoblast differentiation, with an implied role in the ossification process [36]. Finally, COL6A6 has been implicated in the process of vascular smooth muscle cell differentiation from pluripotent progenitors [37].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of seeding cells is one of three critical elements of tissue engineering. Previous investigations have demonstrated that mesenchymal stem cells (MSCs) derived from bone marrow, fat tissues, umbilical cord, or peripheral blood can serve as potential seeding cell sources for bone tissue engineering 17‐20 . However, sources of these stem cells are limited and the invasive isolation procedure is associated with a risk of complications.…”
Section: Introductionmentioning
confidence: 99%